G351(P) High falls from windows and balconies in children (2006–2011). (12th March 2018) - Lewis, SP; Nicholson, AJ
Abstract : Aims: Young children are at risk of falls due to their lack of danger awareness and curious nature. Falls from heights more than two metres are associated with significant risk of death and disability and contributed to 2.7% of injury-related deaths in Ireland between 2006–2011. The aim of this study was to further explore falls from windows and balconies, to identify demographics, injury type and severity, long-term outcomes and to inform strategies for prevention. Methods: This retrospective cohort study reviewed high falls from windows and balconies in children from 2010 to 2016 in Ireland. Data was obtained from submissions to the Trauma Audit and Research Network (TARN) database and analysed in Excel. 1, 2 Results: Seventy-six high falls were recorded during the study period with twenty falls occurring from a window or balcony. Of these twenty children, eighteen were less than five years, with a median age of 2 years (range 1.0–7.6 years) and a male to female ratio of 2.3:1. In this patient cohort, there were two deaths, four children sustained moderate disability and fourteen had a good recovery according to Glasgow Outcome Score (GOS). The head was the most severely injured body part in 75% of falls (15/20). Injury severity score was greater than 15 in 65% (13/20) indicating moderate to severe injury. Although data was not available for all children, it was noted that high falls occured more often in the home than in public places (9 vs. 3 cases) and were onto concrete (14 cases). The two deaths were associated with falls from fourth and fifth floor windows. Conclusions: High falls from windows and balconies, although infrequent, do occur and are preventable. Boys and children under 5 are at highest risk. Education on fall prevention, and environmental modifications such as window guards and alteration of surfaces below windows and balconies may prevent death and serious injury in young children. References: . Committee on Injury and Poison P. American Academy of Paediatrics. Falls from heights: windows, roofs, and balconies. Paediatrics2001;107:1188–91. . Freyne, B, et al. Epidemiology of high falls from windows in children. Irish Medical JournalFebruary 2014;107(2).